PENGARUH RASIO SOLVABILITAS TERHADAP KINERJA KEUANGAN PADA SEKTOR PERBANKAN DI BURSA EFEK INDONESIA PERIODE 2012 – 2016 - Fitria Fitria (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2018)
This research aims to know the magnitude of the influence of Solvency Ratio on performance of the financial of banking sector in the Indonesian stock exchange. The purpose of this research is seen from the problem